SOCIOECONOMIC DYNAMICS AND WILLINGNESS TO PAY FOR WATER SUBSCRIPTION DECISIONS IN PEKANBARU - Isyak Pratama P.; Raras Herry K., Sarah Mulyani, Ovalia (Adisam Publisher, 2025)
High quality drinking water is an essential need for public health and welfare. In Pekanbaru city, clean water supply efforts through the Pekanbaru-Kampar. Drinking Water Supply System (SPAM) which continues to be developed by local government to meet the needs of water suitable for consumption. However, public interest, particularly among potential customers, in SPAM services still varies. This research aims to analyze the socio-economic dynamics of the community and their relationship with willingness to pay (WTP) on the decision to subscribe to water services provided by the Drinking Water Company (PAM) Pekanbaru City. The background of this research is based on the low penetration rate of household clean water services despite the increasing need for access to potable water. Using a qualitative approach and case study method, data was collected through in-depth interviews, observations, and documentation of residents from various socioeconomic backgrounds in the Pekanbaru-Kampar SPAM service area. The results of the research indicate that factors such as household income, education level, perception of service quality, previous experience with water services, and social norms in the surrounding environment significantly influence the community's decision to subscribe. In addition, it was found that willingness to pay is not only influenced by financial capability but also by trust in the service provider institution and perceptions of the value of water as a public necessity. This research recommends community-based approaches and increased service transparency as strategies to enhance customer participation. This research is expected to contribute to the development of more inclusive and equitable clean water policies and promote sustainable development in the public service sector.